International service-learning: possibilities for developing intercultural competence and culturally responsive pedagogies. Issue 2 (15th March 2022) - Wrench, Alison; Neill, Bec; Diamond, Alexandra
ABSTRACT: Globalisation and human mobility have contributed to increased student diversity in Australian schools and globally. Initial Teacher Education (ITE) programmesare under pressure to prepare pre-service teachers (PST) who can respond to the educational and cultural needs of diverse student cohorts. International study tours and service-learning programs are conceived as means for developing interculturally competent "classroom-ready" teachers. This paper reports on a New Colombo Plan water safety/swimming programmedesigned and delivered by pre-service teachers in a rural Fijian community. Findings indicate that immersion as "other" was important for building empathy and appreciation of the lived realties of linguistically and culturally diverse Indigenous Fijian and Indo-Fijian children. Additionally, findings reveal various ways by which PST enacted cultural competence in teaching the water safety/swimming program. Where international service learning is not always be an option, we argue for multiple opportunities for PST to work with children within diverse communities and cultural life-worlds. At stake is the potential of ITE programs to enable the development of pedagogical practices for meeting the cultural and educational needs of all children We believe these calls have relevance for ITE educators and their programs in Australia and the broader Asia-Indo-Pacific region.